Cyberterrorism as a threat to international peace and security: A critical discourse - Mohd Badrol, Awang; Abdullahi Ayoade, Ahmad; Jamal Awwad, Abdallah (2019)
With the end of the previous millennium and the entry of the new millennium, a new and somewhat strange war emerged. With the technological development and the invention of modern computers, this threat has become inevitable and imminent for both big and small countries. The new form of conflict is as challenging to international peace and security as the traditional ones and came with new threats that take place in a virtual battlefield known as cyberspace. Thus, cybercrimes, cyberterrorism and cyberwarfare came under the limelight on the international stage and became one of the primary concern of the world of the United States and other world powers. The western powers started considering cyberterrorism to be same with traditional terrorism and advocate for the application of equal measure to address it. The qualitative descriptive method of data analysis was utilized in making meaning out of the data collected from the secondary sources. It involves a descriptive summary of the information collected on specific events of the issues under study. This paper dwells on the phenomenon of cyberterrorism with inquisition of whether international law applies to cyberspace. Finally, some recommendations are offered on how to address the issue.